Hydraulic force fighting mitigation - HAHN MATTHEW LEE (2024)
The subject matter of this specification can be embodied, inter alia, in a method comprising controlling, by a first fluid valve, a first fluid flow to a first fluid actuator, actuating, by the first fluid actuator, a second fluid flow to a second fluid actuator, by a second fluid valve, and actuating, by the second fluid actuator. 本说明书的主题尤其可体现在下述方法中，该方法包括由第一流体阀控制到第一流体致动器的第一流体流动、由第一流体致动器致动输出器、由第二流体阀控制到第二流体致动器的第二流体流动，并且由第二流体致动器致动输出器。